Chapter 8 Unintended Consequences of EU Democracy Support in the European Neighbourhood - Dandashly, Assem (Taylor & Francis, 2019)
"The European Union's (EU) impact on the political governance of the European neighbourhood is varied and sometimes opposite to the declared objectives of its democracy support policies. The democracy promotion literature has to a large extent neglected the unintended consequences of EU democracy support in Eastern Europe and the Middle East and North Africa. The EU has left multiple imprints on the political trajectories of the countries in the neighbourhood and yet the dominant explanation, highlighting the EU's security and economic interests in the two regions, cannot fully account for the unintended consequences of its policies. The literature on the 'pathologies' of international organisations offers an explanation, emphasizing the failures of the EU bureaucracy to anticipate, prevent or reverse the undesired effects of its democracy support in the neighbourhood."